Dampak Loyalitas Pelanggan Dipengaruhi Oleh Kualitas Produk, Layanan, Dan Kepercayaan Pelanggan - Reni Widiastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to investigate the impact of customer loyalty by focusing on the influence of product quality, service and customer trust. The research method used is a survey involving respondents who are customers from various industrial sectors. Data is collected through questionnaires that share customer perceptions of product quality, service, and their level of trust in the brand or company. The results of data analysis show that product quality, service and customer trust significantly influence the level of customer loyalty. Good product and service quality can increase customer satisfaction, while customer trust is a key factor in building long-term relationships. Therefore, efforts to improve the quality of products, services and build customer trust can be an effective strategy in maintaining and increasing customer loyalty.